Shark heart eaudiobook A love story. - Habeck, Emily (Simon & Schuster Audio, 2023)
A New York Times Editors' Choice A USA TODAY Bestseller A Booklist Editor's Choice A Goodreads Choice Award Nominee A Massachusetts Book Awards Fiction Honors Selection Shortlisted for the Brooklyn Public Library Book Prize A "beautifully written" (Anthony Doerr, Pulitzer Prize–winning author of All the Light We Cannot See ) debut novel of marriage, motherhood, metamorphosis, and letting go, this intergenerational love story begins with newlyweds Wren and her husband, Lewis—a man who, over the course of nine months, transforms into a great white shark. For Lewis and Wren, their first year of marriage is also their last. A few weeks after their wedding, Lewis receives a rare diagnosis. He will retain most of his consciousness, memories, and intellect, but his physical body will gradually turn into a great white shark. As Lewis develops the features and impulses of one of the most predatory creatures in the ocean, his complicated artist's heart struggles to make peace with his unfulfilled dreams. At first, Wren internally resists her husband's fate. Is there a way for them to be together after Lewis changes? Then, a glimpse of Lewis's developing carnivorous nature activates long-repressed memories for Wren, whose story vacillates between her childhood living on a houseboat in Oklahoma, her time with her college ex-girlfriend, and her unusual friendship with a woman pregnant with twin birds. Woven throughout this "heart-wringing" (Adam Roberts, internationally bestselling author of Salt ) novel is the story of Wren's mother, Angela, who becomes pregnant with Wren at fifteen in an abusive relationship amidst her parents' crumbling marriage. In the present, all of Wren's grief eventually collides, and she is forced to make an impossible choice. A sweeping love story that is at once lyrical and funny, airy and visceral, Shark Heart is an unforgettable, gorgeous novel about life's perennial questions, the fragility of memories, finding joy amidst grief, and creating a meaningful life. This daring debut marks the arrival of a wildly talented new writer abounding with originality, humor, and heart.